Penentuan Arah Kiblat Dengan Penerapan teori trigonometri Bola di Kematan Sinjai Utara Kabupaten Sinjai - Nur Chalisha; Rahma Amir (HISABUNA: Jurnal Ilmu Falak, 2020)
There are various methods in measuring Qibla, but the method that is generally used in determining the direction of the Qibla in mosques in North Sinjai District, Sinjai Regency is the application of tools such as the Qiblat Tracker and the Qibla Compass. Apart from these two tools, there is a spherical trigonometric theory which then applies the theory using the Stick Istiwa 'tool to take measurements at mosques. This theory uses calculations by utilizing a triangle on a sphere that connects the three points that are the reference in the calculation. The results of calculations from the trigonometric theory are then compared with the results of measurements in the field. The incidence of skewness towards the direction of the mosque's Qibla is caused when the measurement is only based on the west direction and the tools or methods used are not clear. To minimize the incidence of digression in the direction of the Qibla, it is necessary to disseminate the direction of the Qibla, increase public awareness and increase and increase knowledge and tools of astronomy which will greatly assist in the process of determining a more accurate Qibla direction.Keywords: Qibla Direction, Ball Trigonometry Theory, Stick Istiwa'